2023
DOI: 10.3390/diseases11040150
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Bacteriophage D29 Loaded on Nanoliposomes against Macrophages Infected with Mycobacterium tuberculosis

Ana P. B. Silva,
Cesar Augusto Roque-Borda,
Christian S. Carnero Canales
et al.

Abstract: The search for new antimicrobial agents is a continuous struggle, mainly because more and more cases of resistant strains are being reported. Mycobacterium tuberculosis (MTB) is the main microorganism responsible for millions of deaths worldwide. The development of new antimicrobial agents is generally aimed at finding strong interactions with one or more bacterial receptors. It has been proven that bacteriophages have the ability to adhere to specific and selective regions. However, their transport and admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Additionally, LPs have suitable technological properties, are biocompatible, and have wide versatility to be included in other pharmaceutical forms, such as gels (transdermal administration) or aerosols (dry powder) for pulmonary instillation [ 278 , 283 ]. In addition, liposomes significantly enhance stability and demonstrate an unparalleled ability to traverse challenging biological barriers such as the intestinal membrane, macrophages, and the blood-brain barrier [ 284 ].…”
Section: Nanoscale Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, LPs have suitable technological properties, are biocompatible, and have wide versatility to be included in other pharmaceutical forms, such as gels (transdermal administration) or aerosols (dry powder) for pulmonary instillation [ 278 , 283 ]. In addition, liposomes significantly enhance stability and demonstrate an unparalleled ability to traverse challenging biological barriers such as the intestinal membrane, macrophages, and the blood-brain barrier [ 284 ].…”
Section: Nanoscale Drug Delivery Systemsmentioning
confidence: 99%
“…Researchers have extensively studied nanocarriers including liposomes, polymeric nanoparticles, and lipid-based nanoparticles, for effective anti-TB drug delivery. Preclinical studies have shown promising results, including improved drug effectiveness, lower toxicity, and increased antimicrobial activity against MTB [ 250 , [362] , [363] , [364] , [365] , [366] , [367] ]. Additionally, nanocarriers can load multiple drugs and promote simultaneous drugs delivery [ [368] , [369] , [370] ].…”
Section: Gap Until Clinical Studymentioning
confidence: 99%